Keterlibatan Siklus Terintegrasi Knowledge Management Terhadap Perilaku Kerja Inovatif Sumber Daya Manusia di Balai Diklat Keuangan Yogyakarta: The Involvement of Integrated Knowledge Management Cycle Towards Human Resource Innovative Work Behavior in Financial Education and Training Agency Yogyakarta - Bagas Dwi Praptowo; Mikhriani Michdor; Agus Suharsono (Pusjar SKPP Lembaga Administrasi Negara, 2020)
To realize Knowledge Management as one of pillars of Ministry of Finance Corporate University, Financial Education and Training Agency Yogyakarta as an institution that carries out a role of building a learning environment needs to have a series of systems and procedures for managing financial knowledge so that is available and well managed. This study aims to prove efforts effective influencing Human Resource (HR) Innovative Work Behavior in Financial Education and Training Agency Yogyakarta are through an integrated Knowledge Management Cycle namely Knowledge Capture, Knowledge Sharing and Dissemination, Knowledge Acquisition and Application. This integrated cycle can stimulate HR in critical, creative, and innovative thinking to produce useful new knowledge. This research method was a quantitative approach to SEM analysis using Smart PLS software. The results of the study proved that Knowledge Acquisition and Application affect the HR Innovative Work Behavior. However, Knowledge Capture and Knowledge Sharing and Dissemination did not affect HR Innovative Work Behavior, this indicates that there was a need to increase Knowledge Capture and Knowledge Sharing and Dissemination at Financial Education and Training Agency Yogyakarta so that overall employees could contribute to fostering Innovative Work Behavior in accordance under BPPK Decree No. KEP-140/PP/2017 which regulates that Knowledge Management is all employees’ task of Ministry of Finance. Keywords: Knowledge Capture, Knowledge Sharing and Dissemination, Knowledge Acquisition and Application, Human Resource (HR) Innovative Work Behavior Abstrak Mewujudkan Knowledge Management sebagai salah satu pilar Kemenkeu Corporate University, Balai Diklat Keuangan Yogyakarta sebagai instansi yang menjalankan peran membangun lingkungan pembelajaran, perlu memperhatikan rangkaian sistem dan prosedur dalam mengelola pengetahuan keuangan negara agar tersedia dan terkelola dengan baik. Penelitian ini bertujuan untuk membuktikan bahwa upaya yang dipandang efektif dalam mempengaruhi Perilaku Kerja Inovatif SDM di Balai Diklat Keuangan Yogyakarta adalah melalui siklus terintegrasi dari tiga tahapan Knowledge Management, yaitu Knowledge Capture, Knowledge Sharing and Dissemination, Knowledge Acquisition and Application. Siklus terintegrasi tersebut dapat merangsang SDM untuk berfikir kritis, kreatif, dan inovatif sehingga menghasilkan pengetahuan baru yang berguna. Metode penelitian ini melalui pendekatan kuantitatif analisis SEM menggunakan software Smart PLS. Hasil penelitian membuktikan bahwa Knowledge Acquisition and Application berpengaruh terhadap Perilaku Kerja Inovatif SDM. Namun, Knowledge Capture dan Knowledge Sharing and Dissemination tidak berpengaruh terhadap Perilaku Kerja Inovatif SDM. Hal ini mengindikasikan bahwa perlunya peningkatan Knowledge Capture dan Knowledge Sharing and Dissemination di Balai Diklat Keuangan Yogyakarta agar secara keseluruhan pegawai dapat berkontribusi menumbuhkan Perilaku Kerja Inovatif sesuai Keputusan Kepala BPPK No. KEP-140/PP/2017 yang mengatur bahwa tugas Knowledge Management adalah seluruh pegawai Kemenkeu. Kata kunci: Knowledge Capture, Knowledge Sharing and Dissemination, Knowledge Acquisition and Application, Perilaku Kerja Inovatif SDM